ANALISIS PROGRAM TEPAT DAYA DALAM PEMBERDAYAAN EKONOMI PEREMPUAN PRASEJAHTERA DI PT BTPN SYARIAH MEDAN - Fadhillah, Fadhillah; Asnawi, M; zulkarnain, Mierna (Journal Economic Management and Business, 2024)
Economic empowerment of underprivileged women requires an approach that includes various aspects, ranging from education, skills training, access to resources, to institutional support. This research aims to analyze the Bapa Daya program implemented by PT BTPN Syariah in the economic empowerment of underprivileged women, focusing on the MMS Medan Marelan branch office as a case study. The research method used is descriptive analysis with a qualitative approach. Data was collected using in-depth interviews, observations, with related parties at PT BTPN Syariah Medan as well as documentation studies related to the Bapa Daya program. Research respondents consisted of branch managers, Precise Daya Platfom (TDP) officers, and MSME voters who had utilized the Precise Daya Platfom (TDP) from BTPN Syariah. The research results show that the Bapa Daya program provided by BTPN Syariah has made a significant contribution in increasing the economic independence of underprivileged women in Medan Marelan. This program provides assistance and training in various fields, such as financial management and business skills, which improves women's ability to manage their micro and medium enterprises. Apart from that, this program also facilitates underprivileged women's access to sharia financial services which enable them to develop their businesses sustainably. However, there are still several obstacles faced by program participants, such as limited access to capital and a lack of understanding of sharia financial principles. Therefore, further efforts are needed to increase the effectiveness of the Bapa Daya program, including increasing access to capital and deepening understanding of sharia financial principles for program participants.